Reducing smoking reduces suicidality among individuals with psychosis: Complementary outcomes from a Healthy Lifestyles intervention study. (30th September 2016) - Sankaranarayanan, Anoop; Clark, Vanessa; Baker, Amanda; Palazzi, Kerrin; Lewin, Terry J.; Richmond, Robyn; Kay-Lambkin, Frances J.; Filia, Sacha; Castle, David; Williams, Jill M.
Abstract: This study sought to explore the impact of smoking reduction on suicidality (suicide ideation and behaviour) among people with a psychotic disorder (n=235) who participated in a randomized trial of a healthy lifestyle intervention trial. Suicidality, measured by item −4 of the Brief Psychiatric Rating Scale (BPRS) was the main variable of interest. Measures were collected by research assistants blind to treatment allocation at baseline, at 15 weeks (mid-intervention) and 12 months after baseline. Mediation analysis, adjusted for confounders, was used to determine the relationship between smoking reduction and suicidality and to explore whether this was mediated through depression. At 12 months, smoking reduction was found to be significantly associated with suicidality change; an association was also seen between smoking reduction and depression and depression and suicidality. After adjusting for depression, the association between smoking reduction and suicidality was attenuated but remained statistically significant; the proportion of the total effect that was mediated through depression was 30%. There was no significant association between suicidality and treatment group (vs. controls) over time. Our study suggests that smoking interventions may have benefits over and above those for improved physical health, by reducing suicidal ideation in people with psychosis. Highlights: This study explored impact of smoking reduction on suicidality among people with psychosis. At 12 months, smoking reduction was significantly associated with reduction in suicidality. At 12 months, smoking reduction was significantly associated with reduction in depression. Association between smoking and suicidality change remained statistically significant after adjusting for depression. Depression accounted for only 30% of suicidality associated with smoking.